Africas on one’s mind : studying appropriation in world politics from the africanization of security in Senegal - (:unkn) unknown (My University, 2023)
“African Solutions to African Problems” are put forward today by African actors as well as actors exogenous to Africa, parallel to their own interventions. The theory of extraversion as well as the theory of regime survival would a priori easily explain such contradiction. But it would be part of a broader narrative of invention of Africa, as it has been existing in International Relations literature since the 1960s. To read works produced in Africa, which is not spontaneous for scholars in Western universities, contributes to nuance these theories. As for Senegal for instance, the President has not systematically been an “omnipotent African executive” since independence. Furthermore, ideas (especially those related to Pan-Africanism) and interests are complementary to readings in terms of constraints and voluntary dependency. “African solutions” are as a matter of fact a “moment” in a longer intellectual history that grasps with Africa’s dismemberment since the slave trade and colonization. Appropriation constitutes in that regard a way to constitute a political subjectivity as well as a re-membering. The study of how the Senegalese state came into world politics through appropriation shed light on the forming of the state generally speaking, until today. The wolof expression “moom sa bopp”, that could be translated both by appropriation and independence, and that was a political rallying cry during the 1960s, is a symptom of such porosity between appropriation and independence when they are observed “from Senegal”.
Keywords: African Research